Utilisation of Social Media in Market Research and Business Decision Analysis - Abu Muna Almaududi Ausat; Riko Mersandro Permana; Filda Angellia; Agus Dedi Subagja; Wahyuni Sri Astutik (Jurnal Minfo Polgan, 2023)
In recent years, social media has experienced significant growth and become a very popular platform for individuals and companies. Social media such as Facebook, Twitter, Instagram, and LinkedIn have become important places for people to interact, share information, and express their opinions. This study aims to conduct a review of current literature on the utilisation of social media in market research and business decision analysis. The focus of this study is primarily qualitative. Methods for gathering data include paying close attention to detail while viewing and recording data, and then using analytical techniques such as data reduction, visualisation, and inference to draw conclusions. The study concluded that utilising social media in market research and business decision analysis can provide significant benefits for companies in understanding consumers, identifying market trends, and making smarter business decisions. With direct access to real-time data and user insights, companies can unearth valuable information about their consumers' preferences, behaviours, and needs.